Development of An Adjustable Welding Table for Welding Needs in A Production Workshop PT Envicon Ekatama using the French Method - Agus Widodo; Merdieco Rivandi; P Yudi Dwi Arliyanto; Muhammad Alif Ihsan; Fadil Abdullah; Rizal Prasetyo (Telkom University, 2025)
This research focuses on the development of an adjustable welding table for welding needs in the production workshop of PT. Envicon Ekatama, using the French design method. The background of the research shows that the existing conventional welding table causes discomfort and safety issues for welding operators, such as hunched postures and non-ergonomic overhead positions, as well as table sway that can cause workpieces to fall. The research method involved problem analysis, development of two design concepts using Autodesk AutoCAD 2016, concept confirmation through scoring, and concept detailing. The second concept, which considered high mobility with the addition of wheels and adjustable height settings, was selected as the best design based on operator assessment scores. Comparison of Figures from the Research, Operator comfort of conventional welding table (existing), total comfort score of 12 out of 30. Adjustable welding table (Concept 2) total comfort score of 22 out of 30. Effectiveness of using conventional welding table (existing) total effectiveness score of 16 out of 30. Adjustable welding table (Concept 2) total effectiveness score of 22 out of 30. Increased effectiveness by 37.5%. The designed adjustable welding table allows the operator to adjust the table height according to the workpiece conditions and individual needs, thereby increasing comfort in various welding positions. The design also includes detailed drawings for the base plate, lifting rod, welding table area, and top support, as well as a clear installation sequence.